When it rains ... it rains - Martin, Bill, 1916-; Luzzati, Emanuele, 1921- (New York, Holt, Rinehart and Winston, 1970)
Lists in verse the most obvious quality of any kind of weather or human condition: "When it's cold, it's cold./ ... When you're old, you're old."
Keywords: Stories in rhyme